Perubahan Makna pada Kata Serapan Bahasa Arab dalam Bahasa Indonesia - Umi Kulsum (Buletin Al-Turas, 2010)
This article discusses the change of meaning in Indonesia words borrowed from Arabic.The introduction of the Arabic into Indonesian is inextricably linked to the islamization of NUsantara. THe first significant evidenceof Arabic influence in Nusantara dates from the fourteenth century, and this influences continues to the present dar of Indonesa. The borrowing of Arabic words to Indonesian occurs through adaption of Arabic manuscripts. When there are no  Indonesian equal words, the Arabic will be entirely used. In its development, the changes of Arabic meaning are frequently take place either generalization (extention), specialization (narrowing), metaphor, amelioration or pejoration of meaning. Those changes are caused by some factors, namely 1) social and cultural development 2) association 3) perception difference and4) term development.